Emodin Ameliorates Acute Pancreatitis-Associated Lung Injury Through Inhibiting the Alveolar Macrophages Pyroptosis - Wu, Xiajia; Yao, Jiaqi; Hu, Qian; Kang, Hongxin; Miao, Yifan; Zhu, Lv; Li, Cong; Zhao, Xianlin; Li, Juan; Wan, Meihua; Tang, Wenfu (Frontiers in Pharmacology, 2022)
Objective: To investigate the protective roles of emodin in acute pancreatitis (AP)-associated lung injury and its underlying mechanisms. Methods: NaT-AP model in rats was constructed using 3.5% sodium taurocholate, and CER+LPS-AP model in mice was constructed using caerulein combined with Lipopolysaccharide. Animals were divided randomly into sham, AP, Ac-YVAD-CMK (caspase-1 specific inhibitor, AYC), and emodin groups. AP-associated lung injury was assessed through H&E staining, inflammatory cytokine levels, and myeloperoxidase activity. Alveolar macrophages (AMs) pyroptosis was evaluated by flow cytometry. In bronchoalveolar lavage fluid, the levels of lactate dehydrogenase and inflammatory cytokines were measured by enzyme-linked immunosorbent assay. Pyroptosis-related protein expressions were detected by Western Blot. Results: Emodin, similar to the positive control AYC, significantly alleviated pancreatic and lung damage in rats and mice. Additionally, emodin decreased the pyroptotic rates of AMs, inflammatory cytokines, and the lactate dehydrogenase level. More importantly, the protein expressions of NLRP3, ASC, Caspase1 p10, GSDMD, and GSDMD-NT in AMs were significantly downregulated after emodin intervention. Conclusion: Emodin has a therapeutic effect on AP-associated lung injury, which is at least partially due to the inhibition of NLRP3/Caspase1/GSDMD-mediated AMs pyroptosis signaling ways.